Implementasi Manajemen Pembiayaan dalam Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Madrasah Aliyah Negeri 1 Bitung, Sulawesi Utara - Feiby Ismail; Nindy Sumaila (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to describe the implementation of The School Operational Assistance Fund (BOS) funds finance management in MAN 1 Bitung. BOS aims to relieve the burden of society in terms of education fund. Therefore, proper financial management is needed to achieve its purpose. This research uses qualitative approaches using observation, interviews, and documentation as data collection techniques. The results showed that the implementation of BOS finance management in MAN 1 Bitung was realized through the function of planning, implementation, and supervision. Planning involves formulating a budget draft. Then, the implementation stage is done through socialization and disbursement of funds. The final stage is the supervision stage. Through the implementation of this management function, BOS finance management in MAN 1 Bitung positively impacts the education process. Nevertheless, there is a need to coordinate with every element of the madrasah to ensure accountability for BOS funds.